Resin composition, sheet molding compound, and alumina particles used in resin composition
The resin composition with alumina particles having a specific OH group ratio addresses the challenge of dimensional stability in semiconductor sealing members under repeated heat exposure, achieving effective suppression of dimensional changes and enhanced mechanical properties.
Patent Information
- Application Number
- JP2024155264
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-10
AI Technical Summary
The miniaturization of semiconductor devices and narrowing of wiring pitch have led to strict requirements for the sealing member to maintain dimensions despite heat exposure, as semiconductor devices repeatedly undergo high temperatures, causing significant dimensional changes in the sealing member.
A resin composition containing alumina particles with specific surface characteristics, such as a ratio of isolated OH groups to hydrogen-bonded OH groups less than 0.39, is developed to suppress dimensional changes when repeatedly heated. This composition is used to create a sheet molding compound and alumina particles suitable for resin compositions.
The resin composition effectively suppresses dimensional changes when repeatedly heated, enhancing dimensional stability and rupture stress, making it suitable for use as a sealing member in semiconductor devices.
Smart Images

Figure 2025060437000001 
Figure 2025060437000002 
Figure 2025060437000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to resin compositions and sheet molding compounds, as well as alumina particles for use in the resin compositions. [Background technology]
[0002] Heat generated by passing electricity through electronic components is likely to adversely affect the performance of the electronic components, so it is desirable to dissipate the heat quickly. Therefore, for example, it is desirable for a member constituting a semiconductor sealing member surrounding an IC chip to exhibit high thermal conductivity for heat dissipation. The sealing member may generally contain alumina particles and resin, as described in Patent Document 1. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-200478 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, with the miniaturization of semiconductor devices and the narrowing of wiring pitches, strict requirements have been placed on the sealing member with respect to dimensional change due to heat. In particular, since semiconductor devices can be repeatedly exposed to high temperatures due to current flow, etc., it has become problematic that the dimensions of the sealing member change significantly when repeatedly heated. In the conventional technology as described in Patent Document 1, suppression of dimensional changes caused by repeated heating has not been considered.
[0005] In view of this situation, one embodiment of the present invention aims to provide a resin composition containing alumina particles and a resin, which is capable of suppressing dimensional change when repeatedly heated. Another embodiment of the present invention has an object to provide a sheet-shaped composition (sheet molding compound) comprising such a resin composition. Yet another embodiment of the present invention is directed to providing alumina particles for use in a resin composition. [Means for solving the problem]
[0006] Aspect 1 of the present invention is alumina particles having OH groups on the surface thereof and a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39; and a resin composition comprising the resin.
[0007] Aspect 2 of the present invention is The alumina particles have an isolated OH group count of 3.1 / nm 2 The resin composition of claim 1,
[0008] Aspect 3 of the present invention is The alumina particles have a specific surface area of 0.20 m 2 / g or more.
[0009] A fourth aspect of the present invention is In the resin composition according to any one of Aspects 1 to 3, the alumina particles have a ratio (L2 / L1) of the total length L2 of the internal grain boundaries to the length L1 of the outer edge of the alumina particles is less than 139.1%.
[0010] A fifth aspect of the present invention is The resin composition according to any one of aspects 1 to 4 is used. A sheet molding compound having a thickness of 1000 μm or less.
[0011] A sixth aspect of the present invention is The alumina particles have a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39. Effect of the Invention
[0012] According to one embodiment of the present invention, it is possible to provide a resin composition that contains alumina particles and a resin, and that is capable of suppressing dimensional changes when repeatedly heated. According to another embodiment of the present invention, there is provided a sheet molding compound comprising such a resin composition. According to yet another embodiment of the present invention, alumina particles for use in a resin composition can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have conducted extensive research to realize a resin composition containing alumina particles and a resin, which is capable of suppressing dimensional changes when repeatedly heated. As a result, they have found that by containing alumina particles in which the ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups is less than a predetermined value, dimensional changes when repeatedly heated can be suppressed. This is believed to be because the smaller the ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups, the lower the bonding force between the alumina particles, suppressing aggregation between the alumina particles, and facilitating moderate interactions between the alumina particles and the resin, resulting in improved dimensional stability against external energy such as heat.
[0014] The resin composition according to this embodiment, the alumina particles used in the resin composition, and the sheet molding compound (SMC) made of the resin composition will be described below. In this specification, the term "resin composition" is intended to include all of the resin compositions in the liquid state before the resin in the resin composition is cured, the semi-cured state (B stage) in which the resin is semi-cured, and the cured state (C stage) in which the resin is completely cured. Here, the "liquid state" includes compositions in which the resin composition has fluidity, such as resin compositions containing a solvent described below. The "semi-cured state" refers to a state in which the resin composition is cured to an extent that it can be handled as a solid, but is not completely cured, and therefore the surface of the resin composition is sticky. The "cured state" refers to a state in which the resin composition can be handled as a solid and has almost no stickiness on the surface.
[0015] [Resin composition] The resin composition according to the present embodiment contains alumina particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39, and a resin, which can suppress dimensional changes when repeatedly heated.
[0016] The alpha dose of the resin composition is 0.022 cph / cm 2 It is preferable that the dose of α-rays is less than 0.020 cph / cm. This is because semiconductor devices are easily affected by α-rays, and malfunctions (soft errors) caused by α-rays are likely to become a problem. Furthermore, if the dose of α-rays is low, damage to the semiconductor element is small, adhesion at the interface between the resin composition and the element is easily maintained, and deformation due to thermal history is easily suppressed. The α-ray dose of the resin composition is preferably 0.020 cph / cm. 2 or less, more preferably 0.015 cph / cm 2 Less than 0.005 cph / cm, more preferably 0.005 cph / cm 2 Less than 0.002 cph / cm is particularly preferable. 2 In particular, the alpha radiation dose of the cured resin composition is 0.022 cph / cm 2 Less than 0.020cph / cm 2 Below, 0.015cph / cm 2 Below, 0.005cph / cm 2 Less than or equal to 0.002cph / cm 2The lower the alpha dose of the resin composition, the more preferable. The lower limit is preferably 0.000 cph / cm 2 The alpha radiation amount of the resin composition is measured in a semi-cured or cured state using an alpha radiation measuring device (e.g., Model 1950 manufactured by Alpha Sciences, Inc.). The measurement area of the sample is 1000 cm. 2 The measurement time is 99 hours, and the counting gas used is PR-10 gas (Ar 90%, CH4 10%).
[0017] The elastic modulus (tensile elastic modulus) of the resin composition is preferably 2.0 GPa or more. The elastic modulus of the resin composition is more preferably 3.0 GPa or more, even more preferably 4.0 GPa or more, even more preferably 5.0 GPa or more, particularly preferably 6.0 GPa or more, and most preferably 7.0 GPa or more. The elastic modulus is measured in a semi-cured or cured resin composition. In particular, the elastic modulus of the cured resin composition is preferably 2.0 GPa or more, and a sealing member that can withstand deformation under general use conditions can be formed. The elastic modulus of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The elastic modulus of the semi-cured and cured resin compositions can be increased by adjusting the content of alumina particles and the curing conditions. Usually, the elastic modulus of the cured resin composition is higher than that of the semi-cured resin composition.
[0018] The rupture stress of the resin composition is preferably more than 41.2 MPa, more preferably 50.0 MPa or more, even more preferably 60.0 MPa or more, and particularly preferably 65.0 MPa or more. The rupture stress of the resin composition is measured in a semi-cured or cured state. In particular, the rupture stress of the cured resin composition is preferably more than 41.2 MPa, 50.0 MPa or more, 60.0 MPa or more, or 65.0 MPa or more, in that order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The rupture stress of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The rupture stress of the semi-cured and cured resin compositions can be increased by adjusting the content of alumina particles and the curing conditions. Usually, the rupture stress of the cured resin composition is higher than that of the semi-cured resin composition.
[0019] The blending ratio of the alumina particles is preferably in the order of 5-75% by volume of resin, 95-25% by volume of alumina particles, or 8-50% by volume of resin, 92-50% by volume of alumina particles, or 10-40% by volume of resin, 90-60% by volume of alumina particles, or 12-40% by volume of resin, and 88-60% by volume of alumina particles, in the total resin composition. This makes it easier to control the breaking stress and the absorbed energy until breaking of the resin composition to a desired value. In addition, in the semi-cured and cured resin compositions, the total ratio of the resin and the alumina particles to the total resin composition is preferably 60% by volume or more, more preferably 70% by volume or more, and even more preferably 80% by volume or more. In addition, in the semi-cured and cured resin compositions, the ratio of the solid content to the total resin composition is preferably 80% by volume or more, more preferably 90% by volume or more, and even more preferably 95% by volume or more. The solid content of a resin composition refers to what remains as a solid when the resin composition is heated, excluding, for example, the solvent and other components that volatilize upon heating. On the other hand, even if a component is liquid at 25°C, if it is incorporated into the solid content of the resin composition when heated, it is included in the solid content. The proportion of the solid content can be determined, for example, by determining the amount of solvent in the resin composition and subtracting it from the total. The amount of solvent in the resin composition can be measured, for example, by the following method. After measuring the mass W1 (g) of the resin composition, the sample is heated at 150°C for 10 minutes using a total exhaust oven to evaporate all the solvent contained in the sample, and then the sample is left at room temperature for 5 minutes to return to room temperature, and the mass W2 (g) of the sample after heating is measured. The amount of solvent in the resin composition can be determined by subtracting W2 (g) from W1 (g).
[0020] The resin composition of the present invention has a small dimensional change when repeatedly heated, and has excellent dimensional stability. In the present invention, the dimensional stability can be evaluated by measuring the CTE twice and then calculating the CTE change rate from the following formula (1). The CTE change rate is preferably less than 8.5, more preferably 8.4 or less, even more preferably 8.0 or less, even more preferably 7.0 or less, and particularly preferably 6.0 or less. CTE change rate (%) = (CTE at first measurement – CTE at second measurement) / (CTE at first measurement) × 100 (1)
[0021] Next, the alumina particles and the resin that constitute the resin composition will be described in detail.
[0022] [Alumina particles] The alumina particles according to this embodiment have a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39. This suppresses aggregation of the alumina particles in the resin composition, and facilitates moderate interaction between the alumina particles and the resin. The ratio is more preferably 0.35 or less, and even more preferably 0.30 or less. The lower limit of the ratio is not particularly limited, but may be, for example, 0.01 or more. From the viewpoint of facilitating interaction between the particles and the resin, the ratio is preferably 0.03 or more, and even more preferably 0.05 or more. The alumina particles may have OH groups on their surfaces by reacting with moisture in the air, etc.
[0023] The alumina particles according to this embodiment have an isolated OH group count of 3.1 / nm 2 It is preferable that the number of isolated OH groups is less than 2.8 / nm. This can further suppress aggregation of particles in the resin composition, and as a result, the dimensional stability and breaking stress against external energy such as heat can be improved. 2 More preferably, the number of isolated OH groups is 2.5 / nm 2 More preferably, the number of isolated OH groups is 2.0 / nm 2 More preferably, the number of isolated OH groups is 1.5 / nm 2 On the other hand, it is particularly preferable that the number of isolated OH groups is less than 0.1 / nm 2 It is preferable that the number of isolated OH groups is 0.2 / nm or more. This makes it easier for an appropriate interaction to occur between the particles and the resin. 2 More preferably, it is 0.3 particles / nm 2 More preferably, it is equal to or greater than this.
[0024] In this embodiment, the number of isolated OH groups and the number of hydrogen-bonded OH groups of the alumina particles can be quantified using the measurement results by the Karl Fischer method (moisture vaporization-titration method) in accordance with the description of JIS K 0068:2001 "Method for measuring moisture in chemical products". The moisture detected in the Karl Fischer measurement can be considered to be derived from the OH groups of the alumina particles, and the moisture detected at a temperature of 550°C can be considered to be derived from the hydrogen-bonded OH groups, and the moisture detected at a temperature of 900°C can be considered to be derived from the isolated OH groups. The moisture detected in the Karl Fischer measurement is considered to be one water molecule formed by condensing two OH groups, and the number of OH groups can be calculated by the following formula (2). Number of OH groups [pcs / nm 2 ] = 0.0662 × (water content [ppm]) / (specific surface area of alumina particles [m 2 / g]) · · · (2)
[0025] In quantifying the number of isolated OH groups and the number of hydrogen-bonded OH groups of the alumina particles in the resin composition, the resin contained in the resin composition is first removed, for example, by dissolving it in an organic solvent, to separate only the alumina particles. The numbers of isolated OH groups and the number of hydrogen-bonded OH groups can be quantified using the separated alumina particles in the same manner as described above.
[0026] The alumina particles according to this embodiment have a specific surface area of 0.20 m 2 / g or more. This facilitates appropriate interaction between the particles and the resin. The specific surface area is 0.36 m 2 More preferably, the specific surface area is greater than 0.40 m 2 / g or more, and the specific surface area is preferably 0.45 m 2 / g or more, and the specific surface area is preferably 0.55 m 2 It is particularly preferable that the specific surface area is 3.00 m / g or more. 2 / g or less, preferably 2.50m 2 / g or less. In this embodiment, the specific surface area of the alumina particles is a nitrogen adsorption BET specific surface area, and is measured in accordance with JIS-Z8830 (2013). When the alumina particles are contained in a resin composition, the resin contained in the resin composition is removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, and only the alumina particles are separated, and the specific surface area can be measured using the alumina particles.
[0027] By reducing the grain boundary content in the alumina particles, the shielding effect against alpha rays generated from uranium and thorium in the alumina particles can be improved, and the amount of alpha rays emitted from the alumina particles can be reduced. In this embodiment, the ratio of the total length L2 of the grain boundaries to the length L1 of the outer edge (L2 / L1) is introduced as an index of the content of grain boundaries inside an alumina particle. L1 and L2 are determined by observing a cross section of the alumina particle.
[0028] When the length of the outer edge of one alumina particle is L1 and the total length of the grain boundaries of the alumina particle is L2, it can be said that alumina particles with a small value of L2 / L1 have a small content of grain boundaries and emit a low amount of α-rays. In particular, it is preferable that (L2 / L1) (%) is less than 139.1%, which can further reduce the amount of α-rays emitted when used as a filler for a resin composition. By reducing the amount of α-rays emitted from the alumina particles, the amount of α-rays emitted from a resin composition containing the alumina particles can also be reduced.
[0029] (L2 / L1) is preferably 120.0% or less, more preferably 100.0% or less, even more preferably 80.0% or less, even more preferably 60.0% or less, particularly preferably 52.0% or less, and most preferably 50.0% or less. The lower limit of (L2 / L1) is not particularly limited, but may be 10.0% or more, for example, 20.0% or more, 30.0% or more, 40.0% or more, or 43.0% or more. When the lower limit of L2 / L1 is within the above range, the interaction between the particles and the resin becomes easier to work, and the mechanical strength such as the breaking stress of the resin composition is easily increased. This L2 / L1 value becomes particularly large when alumina particles are produced by the flame fusion method using granulated raw material particles or polycrystalline raw material particles, and it cannot be significantly reduced even by performing a post-process such as reheating.
[0030] The "total length L2 of grain boundaries" refers to the sum of the grain boundaries contained inside an alumina particle, and does not include the outer edge of the alumina particle. The total length L2 of grain boundaries is the sum of the total length L3 of grain boundaries inside an alumina particle and the total length L4 of the inner wall of the cavity (if there is a cavity inside the alumina particle) (i.e., L2 = L3 + L4). In addition, when alumina particles are contained in the resin composition, the resin contained in the resin composition can be removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to thermally decompose the resin, and only the alumina particles can be isolated, and L2 / L1 can be measured using the alumina particles.
[0031] Alumina particles with a sharp particle size distribution are preferred because they facilitate moderate interaction between the particles and the resin. For example, the ratio D90 / D50 of the particle size D90 (hereinafter sometimes simply referred to as "D90") of the cumulative 90% of the number of particles from the fine particle side of the cumulative particle size distribution to the particle size D50 (hereinafter sometimes simply referred to as "D50") of the cumulative 50% of the number of particles from the fine particle side of the cumulative particle size distribution is preferably 5.0 or less. D90 / D50 is more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 1.5 or less.
[0032] On the other hand, if the particle size distribution of the alumina particles is broad to some extent, the filling property is improved by allowing small particles to enter the gaps between the large particles, and more alumina particles can be kneaded into the resin, which can increase the dimensional stability and breaking stress against external energy such as heat. Therefore, D90 / D50 is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more.
[0033] The D50 of the alumina particles is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, even more preferably 10 μm or less, particularly preferably 5 μm or less, and most preferably 3 μm or less. By having D50 within the above range, a resin composition suitable for miniaturizing semiconductor devices and narrowing the wiring pitch can be formed.
[0034] In this embodiment, the D90 and D50 of the alumina particles can be determined by measuring the particle size distribution of the alumina particles by a laser diffraction method using, for example, a Microtrack MT3300EXII manufactured by Microtrack Bell Co., Ltd. as a laser particle size distribution measuring device. The particle size of the alumina particles in the resin composition can be measured by removing the resin contained in the resin composition, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, isolating only the alumina particles, and using the alumina particles.
[0035] Another method for determining D90 and D50 of alumina particles is a method using image analysis. The resin composition may be subjected to cross-sectional observation with an SEM, and all alumina particles contained in a predetermined observation area (e.g., 200 μm×200 μm) may be subjected to image analysis, and the particle diameters equivalent to D90 and D50 may be calculated based on the measurement results of their particle diameters (circle equivalent diameters).
[0036] The alumina particles according to the present embodiment preferably have a uranium content of less than 550 ppb and a thorium content of less than 10 ppb. The uranium content and thorium content of the alumina particles are suppressed to very small amounts as described above, so that the amount of α-rays emitted from the alumina particles can be reduced, and as a result, the amount of α-rays emitted from the resin composition can be suppressed. This makes it possible to suppress malfunction of the semiconductor device due to α-rays when used as an encapsulating material for the semiconductor device. In addition, the alumina particles preferably contain α-alumina particles. α-alumina is expected to have an effect of reducing the amount of α-rays emitted from the alumina particles, and the presence of α-alumina particles in the alumina particles can improve the effect of suppressing the amount of α-rays emitted from the resin composition.
[0037] The uranium content is preferably 300 ppb or less, more preferably 100 ppb or less, even more preferably 50 ppb or less, particularly preferably 30 ppb or less, for example 10 ppb or less, or 5 ppb or less. The lower limit of the uranium content is not particularly limited, but may be 0.1 ppb or more. The thorium content is preferably 8 ppb or less, more preferably 5 ppb or less, and particularly preferably 2 ppb or less. The lower limit of the thorium content is not particularly limited, but may be 0.1 ppb or more. The uranium and thorium contents can be measured using inductively coupled plasma mass spectrometry (ICP-MS). When alumina particles are contained in the resin composition, the resin contained in the resin composition can be removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, and the alumina particles alone can be isolated. The uranium content and thorium content can then be measured using the alumina particles.
[0038] [Method of manufacturing alumina particles] The alumina particles according to this embodiment can be produced, for example, by the method described below.
[0039] (Raw alumina) The raw alumina is produced by a known method, such as the Bayer method, the ammonium alum method, the ammonium aluminum carbonate hydroxide method (AACH method), the solvent extraction method, the organoaluminum hydrolysis method (aluminum alkoxide method), the CZ method, the Verneuil method, the chiroporous method, the Bridgman method, the EFG method, or other melt growth methods.
[0040] In the case of the Bayer process, raw alumina can be produced by calcining aluminum hydroxide obtained from bauxite. In addition, the ammonium alum process, the AACH process, the solvent extraction process, and the aluminum alkoxide process are preferable because they can produce high-purity raw alumina with low uranium and thorium contents. If raw alumina produced by these methods, in which the uranium content is suppressed to, for example, less than 550 ppb and the thorium content is suppressed to, for example, less than 10 mass ppb, is used for the production of alumina particles, it is preferable because alumina particles with reduced uranium and thorium contents can be obtained.
[0041] (Crushing raw alumina) In order to easily obtain alumina particles of a desired size by flame melting, the raw alumina is pulverized to obtain an alumina raw powder to be subjected to flame melting. The raw alumina can be pulverized by a known method such as a vibration mill, a bead mill, a ball mill, or a jet mill, and may be pulverized in either a dry or wet state.
[0042] In the above-mentioned pulverization, a surface protective agent may be used. The surface protective agent may not only protect the surface of the alumina raw material powder after pulverization, but also have the function of inactivating the surface of the alumina raw material powder. The surface protective agent can reduce the aggregation of the alumina raw material powders themselves due to its function of inactivating the surface, and is therefore suitable for obtaining alumina particles of a desired particle size after flame fusion using raw material alumina with a high BET specific surface area that is prone to aggregation. Suitable surface protective agents include, for example, monohydric alcohols such as methanol, ethanol, 1-propanol, and 2-propanol; glycols such as ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol; amines such as triethanolamine; and higher fatty acids such as palmitic acid, stearic acid, and oleic acid. Of these surface protective agents, one type may be used alone, or two or more types may be used in combination. Of these, glycols are preferred, and in particular, one or more types of ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol are preferred.
[0043] For example, polyethylene glycol and polypropylene glycol, which are preferably used as surface protective agents, are not particularly limited in terms of their molecular weight, but liquid ones with an average molecular weight of about 200 to 600 are preferred for ease of addition.
[0044] The amount of the surface protective agent added is preferably 0.01 parts by mass or more in order to fully exert the effect of the surface protective agent when the raw material alumina is taken as 100 parts by mass, and is preferably 10 parts by mass or less because the effect of the surface protective agent becomes saturated if the amount of the surface protective agent added is too large. The amount of the surface protective agent added is more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.
[0045] (Flaming) The flame fusion method is a method in which raw alumina is sprayed into a flame, turned into droplets, and then cooled and solidified. According to the flame fusion method, alumina particles can be obtained while maintaining the particle size of the raw alumina. In the flame fusion method, the temperature of the flame fusion furnace is preferably 1000°C or higher. In particular, in the flame fusion method, by setting the raw material supply rate to 50 kg / h or less, preferably 10 kg / h or less, the amount of thermal energy applied to the alumina particles can be controlled within a predetermined range, making it easier to obtain alumina particles that meet the above-mentioned predetermined requirements.
[0046] After the flame melting, the alumina particles are collected by a cyclone and / or a bag filter and classified to obtain alumina particles having desired properties.
[0047] The number of isolated OH groups and the number of hydrogen-bonded OH groups of the alumina particles can be controlled by the conditions of the manufacturing method of the raw alumina, the pulverization method, and the flame fusion method, but can also be controlled by immersing the obtained alumina particles in an acidic solution such as hydrochloric acid. The type of acidic solution used during immersion is preferably hydrochloric acid because of the ease of concentration adjustment. The concentration of the acidic solution is preferably adjusted to 1M to 12M, more preferably 1M to 10M, and particularly preferably 2M to 5M. The mass ratio during immersion is preferably alumina particles:acidic solution of 1:2 to 1:10. The immersion time is preferably 5 hours or more. During immersion, heating may be performed appropriately to shorten the immersion time, for example, heating may be performed to 50 to 90°C. After immersion, washing and drying are preferably performed.
[0048] [resin] The resin used in the resin composition preferably contains one or more selected from the group consisting of epoxy resins and thermoplastic polyimides, and more preferably contains an epoxy resin. Preferred epoxy resins include mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins. The mesogenic epoxy resin is an epoxy resin having a mesogenic group, and is preferably a resin that exhibits a phase transition temperature in the temperature range of 100°C to 200°C to be sealed and exhibits liquid crystallinity. The resin contained in the resin composition may contain one or more epoxy resins. That is, the resin contained in the resin composition may contain one or more epoxy resins selected from the group consisting of mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins, and may further contain a thermoplastic polyimide. These resins are expected to have an effect of shielding alpha rays that may be emitted from alumina particles. Furthermore, by using these resins, it becomes easier to obtain a resin composition having high dimensional stability against external energy such as heat.
[0049] Furthermore, these resin compositions may be appropriately mixed with known additives such as plasticizers, curing agents, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weather resistance agents, antiblocking agents, antistatic agents, leveling agents, and release agents, either singly or in combination, as long as the effects of the invention are not impaired. In addition, as an embodiment of the present application, the resin composition (particularly, a resin composition in a liquid state or a semi-cured state) may contain a solvent, and when the resin composition contains a solvent, it is easy to flow, can be easily deformed to match the fine structure of the IC chip and the substrate, and can seal the dense structure without gaps. As the solvent, a known solvent can be used, and is not limited as long as it can dissolve the resin, and examples of the solvent include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, amine-based solvents, amide-based solvents, halogen-based solvents, hydrocarbon-based solvents, and nitrile-based solvents. Ketone-based solvents and ester-based solvents are preferred from the viewpoint of being good solvents for epoxy resins and excellent coating properties of the resulting resin composition.
[0050] In a preferred embodiment of the present invention, the resin composition comprises alumina particles, an epoxy resin, a solvent, and a hardener, such as an amine-based hardener such as 4,4-diaminodiphenylmethane.
[0051] [Method of producing resin composition] A method for producing the resin composition will be described. A resin composition can be obtained by mixing the alumina particles according to the present embodiment with a resin using a commonly used known method. For example, when the resin is liquid (e.g., liquid epoxy resin, etc.), the resin composition can be obtained by mixing the liquid resin, alumina particles, and a curing agent, and then curing with heat or ultraviolet light. Known curing agents and known methods can be used as the curing agent, mixing method, and curing method. On the other hand, when the resin is solid (e.g., epoxy resin, polyolefin resin, acrylic resin, etc.), the alumina particles and the resin are mixed, and then kneaded by a known method such as melt kneading, or the resin, alumina particles, and a curing agent are dissolved and mixed in a solvent to obtain the desired resin composition. The resin composition may contain a solvent.
[0052] The resin composition according to this embodiment includes a resin composition in all states, including a liquid state before the resin in the resin composition is cured, a semi-cured state (B stage) in which the resin is semi-cured, and a cured state (C stage) in which the resin is completely cured. The resin composition in a liquid state includes a compound in which alumina powder and a resin are mixed in a predetermined mixing ratio, a mixture obtained by mixing the compound, and a molded product obtained by molding the mixture. The semi-cured resin composition includes a resin composition obtained by semi-curing a resin contained in a mixture or a molded product. The cured resin composition includes a resin composition obtained by completely curing a resin contained in a mixture, a molded product, or a semi-cured product.
[0053] [Sheet Molding Compound (SMC)] The resin composition according to the embodiment can be used to provide a sheet molding compound (SMC). The SMC is a resin composition molded into a sheet. The SMC is preferably one that has flowability when heated and pressurized, and may be in a semi-cured state. The thickness of the SMC is preferably 1000 μm or less, and when incorporated into a semiconductor device, the semiconductor device can be made smaller and lighter, and when sealing an IC chip, the sealing performance can be improved. The thickness is more preferably 800 μm or less, even more preferably 600 μm, even more preferably 500 μm or less, particularly preferably 400 μm or less, and particularly preferably 300 μm or less. The lower limit of the thickness is not particularly limited, but from the viewpoint of the dimensions of SMCs generally used and improving the sealing performance of IC chips, it may be, for example, 10 μm or more, 50 μm or more, or even 100 μm or more, or 150 μm or more.
[0054] The SMC can be produced by a known method. As an example, an uncured resin composition is applied onto a substrate, a protective film is placed thereon, and the resin composition is semi-cured. As another example, an uncured resin composition containing a solvent is applied onto a substrate, the solvent is removed from the resin composition by drying or the like, and then a protective film is placed. When using the SMC, the protective film is peeled off, the SMC is pressed against a wafer or the like, the substrate is removed, and the SMC is post-cured.
[0055] The resin composition and SMC according to this embodiment are suitable as sealing materials for semiconductor elements because they can suppress dimensional changes when repeatedly heated. EXAMPLES
[0056] [Preparation of alumina particles] The alumina particles (A to D) used in the resin compositions of Samples No. 1 to 6 were prepared as follows.
[0057] (Alumina particles A and B used in samples No. 1 to 4) Alumina particles A (used for samples Nos. 2 and 4) and alumina particles B (used for samples Nos. 1 and 3) described below were prepared.
[0058] The raw alumina used was γ-alumina obtained by the ammonium alum method (the average particle size of the primary particles calculated from the BET specific surface area value below was 13 nm). The BET specific surface area of this γ-alumina measured by the nitrogen adsorption method was 120 m 2 Before pulverization, 4% by mass of propylene glycol was added as a surface protective agent to the raw alumina and mixed.
[0059] Next, the alumina was processed using a jet mill pulverizer (horizontal jet mill pulverizer PJM-280SP manufactured by Japan Pneumatic Mfg. Co., Ltd.) under the conditions of a feed rate of the raw alumina of 30 kg / h and a gauge pressure of the air supply port during pulverization of 0.5 MPa, to obtain an alumina raw powder with an average secondary particle size of approximately 2 μm.
[0060] The obtained alumina raw material powder was put into a flame melting furnace and melted to obtain spherical alumina particles. The atmospheric temperature in the flame melting furnace was set to 1250°C, and the raw material supply rate was set to 5 kg / h. The obtained alumina particles were collected in a cyclone and classified by cyclone classification to remove particles of 20 μm or more to obtain alumina particles A (D50=5.1 μm, used for samples No. 2 and 4). Furthermore, particles of 10 μm or more were removed to obtain alumina particles B (D50=2.3 μm, used for samples No. 1 and 3).
[0061] (Alumina particle C used in sample No. 5) For sample No. 5, alumina particles C prepared by the following procedure were used. Alumina raw material particles made of single crystal alumina with a D50 of 3.5 μm were prepared, and the raw material supply rate was set to 50 kg / h or less, and the raw material was charged into a flame melting furnace and melted to obtain spherical alumina particles. The obtained alumina particles were classified by cyclone classification, and particles of 20 μm or more were removed to obtain alumina particles C.
[0062] (Alumina particle D used in sample No. 6) For sample No. 6, alumina particles (alumina particles D) manufactured by Denka DAW05 were used.
[0063] The alumina particles used in each sample were subjected to the following measurements.
[0064] [Number of isolated OH groups and hydrogen-bonded OH groups on alumina particles] The number of isolated OH groups and hydrogen-bonded OH groups on alumina particles was quantified using the results of measurement by the Karl Fischer method (moisture vaporization-titration method) in accordance with JIS K 0068:2001 "Method for measuring moisture in chemical products." Moisture detected in the Karl Fischer measurement was considered to be derived from OH groups on alumina particles, moisture detected at a temperature of 550°C was derived from hydrogen-bonded OH groups, and moisture detected at a temperature of 900°C was derived from isolated OH groups. The moisture detected in the Karl Fischer measurement is considered to be one water molecule formed by condensation of two OH groups, and the number of OH groups was calculated by the following formula (2). Number of OH groups [pcs / nm 2 ] = 0.0662 × (water content [ppm]) / (specific surface area of alumina particles [m 2 / g]) · · · (2)
[0065] [Particle size distribution of alumina particles] The D50 and D90 of the alumina particles were measured by the laser diffraction method using a Microtrack MT3300EXII laser particle size distribution measuring device manufactured by Microtrack Bell Co., Ltd. The D50 and D90 were obtained from the particle size distribution measurement results. As a sample for measurement, alumina particles to be measured were added to a 0.2 mass% sodium hexametaphosphate aqueous solution so that the laser scattering intensity was appropriate, and the alumina particle dispersion was dispersed for 5 minutes using the built-in ultrasonic of 40W. The refractive index of alumina was set to 1.76.
[0066] [BET specific surface area of alumina particles] The specific surface area was measured using a Shimadzu Flowsorb III 2310 specific surface area measuring device, and the nitrogen adsorption BET specific surface area was determined by the single point nitrogen adsorption method according to the method specified in JIS-Z8830 (2013). The measurement conditions were as follows: Carrier gas: Nitrogen / helium mixed gas Filling sample amount: 0.1g Sample pretreatment conditions: 200°C for 20 minutes Nitrogen adsorption temperature: Liquid nitrogen temperature (below -196℃) Nitrogen desorption temperature: room temperature (approximately 20°C)
[0067] [Measurement of the outer edge length L1 of an alumina particle and the total length L2 of the grain boundary inside the particle] Cross-sectional observation specimens were prepared using alumina particles of samples No. 1 to 6. In preparing the cross-sectional observation specimens, the alumina particles were embedded in resin for cross-sectional observation, and then the resin and the alumina particles were cut with a diamond cutter. Then, Pt was vapor-deposited on the cross section as a protective film, the cross section was prepared by Ar ion milling, and the specimen was fixed to the SEM specimen stage with Cu double-sided tape, and SEM-EBSD measurement was performed without vapor deposition. The observation position was determined so that two or more alumina particles were completely within the observation area (i.e., two or more alumina particles did not come into contact with the frame of the observation area). All of the measured alumina particles were α-alumina particles.
[0068] The following equipment was used for sample preparation and EBSD measurement: ·Equipment used Ion milling device: IM-4000 (manufactured by Hitachi, Ltd.) Ion sputtering device: E-1030 (manufactured by Hitachi, Ltd.) Ultra-high resolution field emission scanning electron microscope: JSM-7800F Prime (manufactured by JEOL Ltd.) Backscattered electron diffraction equipment: Digiview V (TSL)
[0069] The EBSD measurement conditions were as follows: ·Measurement area: 500.0μm×400.0μm Acceleration voltage: 20.0 kV Magnification: x500 ·Vacuum degree: 30Pa
[0070] In the obtained EBSD image, two or more alumina particles that were not in contact with the frame of the observation area were selected, and the outer edge length L1 of each alumina particle was averaged using image processing software Image J (National Institute of Health). The "total grain boundary length L2" is the sum of the grain boundaries contained inside the alumina particle, and does not include the outer edge of the alumina particle. The total grain boundary length L2 was calculated by adding the total length of the grain boundaries inside the alumina particle and the total length of the inner wall of the cavity (if there is a cavity inside the alumina particle).
[0071] The ratio of the total grain boundary length L2 to the outer edge length L1 (L2 / L1) is expressed as a percentage (%). The more grain boundaries and cavities there are inside the alumina particle, the higher the value of L2 / L1 (%).
[0072] [Uranium and thorium content of alumina particles] The uranium content (U amount) and thorium content (Th amount) contained in the alumina particles were measured as follows. First, the alumina particles were put into a mixed aqueous solution of sulfuric acid and phosphoric acid, and heated to dissolve the alumina particles, to prepare an aqueous solution. Then, the aqueous solution was contacted with a cyclohexane solution of tributyl phosphate, which is commonly used as an extractant for uranium, to extract the uranium contained in the aqueous solution. Then, the uranium transferred to the aqueous phase by back-extraction by contacting again with pure water was measured by the intensities of U238amu and Th232amu using ICP-MS. A standard solution manufactured by SPEX was used to create a calibration curve.
[0073] [Amount of alpha rays emitted from alumina particles] The amount of alpha radiation emitted from the alumina particles was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).
[0074] [Preparation of resin composition] Alumina particles, resin, etc. were kneaded to prepare resin compositions (samples No. 1 to 6). The types of resins used are shown in Table 1, and the amounts of alumina particles used are shown in Table 3. In addition, the elastic modulus of the resin not containing alumina particles was measured when cured, and is shown in the "Elastic Modulus" column of "Resin" in Table 3. Specifically, the resin compositions of Samples No. 1 to 6 were prepared according to the following preparation method. The "resin composition" in Table 3 indicates the resin composition in a cured state.
[0075] (1) Preparation of varnish A 30% by mass mixed solution was prepared by dissolving the resin shown in Table 1 in the solvent shown in Table 1. Furthermore, a curing agent (4,4-diaminodiphenylmethane (manufactured by TCI)) was added in an amount of 0.074% by mass relative to 100% by mass of the mixed solution to prepare a varnish.
[0076] (2) Preparation of alumina / varnish mixture Alumina particles were added to the obtained varnish and kneaded using a planetary centrifugal mixer (manufactured by Thinky Corporation) to prepare an alumina / varnish mixture.
[0077] (3) Film formation The obtained alumina / varnish mixture was applied onto a PET substrate, and a film was formed using an applicator so that the film thickness after thermal curing would be 150 to 200 μm, thereby obtaining a resin composition before curing.
[0078] (4) Heat curing The obtained resin composition before curing was left to stand at room temperature for 1 hour, then heated at 140°C for 15 minutes, and further vacuum press molded at 140°C for 20 minutes at a pressure of 0.5 MPa using a press molding machine, and then heated at 180°C for 120 minutes at normal pressure to be thermally cured. In this way, cured resin compositions (samples No. 1 to 6) were obtained. In the resin compositions of samples No. 1 to 5, the proportion of solids in the entire resin composition was 95% by volume or more.
[0079] [Table 1]
[0080] Details of the resin types listed in Table 1 are as follows:
[0081] Mesogenic epoxy resin (A) It is a prepolymer obtained by reacting trans-4-{4-(2,3-epoxypropoxy)phenyl}cyclohexyl 4-(2,3-epoxypropoxy)benzoate (an epoxy resin represented by the structural formula below) with 6-hydroxy-2-naphthoic acid.
[0082] [ka]
[0083] Mixture of JP-100 and HP6000 The resin was prepared by mixing JP-100 (manufactured by Nippon Soda Co., Ltd.), an epoxidized polybutadiene, and HP-6000 (manufactured by DIC Co., Ltd.), a naphthalene-based epoxy resin, in a mass ratio of 1:9.
[0084] [Elastic modulus and breaking stress of resin composition] The elastic modulus and breaking stress of the resin composition were measured in accordance with JIS K7161 (2014). Specifically, a tensile test was performed under the following conditions, and the obtained stress-strain curve was analyzed and calculated. Test equipment: Autograph AGS-X (Shimadzu Corporation) Load cell: 1kN - Test piece size: 100mm x 10mm Test environment: 22℃ / 59%RH Analysis software: TRAPEZIUMX
[0085] [α-ray dose emitted from resin composition] The amount of α-rays emitted from the resin composition was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).
[0086] [Dimensional change of resin composition when repeatedly heated] The dimensional change of the resin composition when repeatedly heated was evaluated as follows. First, the coefficient of thermal expansion (CTE) was determined in the temperature range of 27° C. to 150° C. by thermomechanical analysis in accordance with JIS K7197. The analysis conditions are shown below. Equipment: TMA7100 (Hitachi High-Tech Science) Measurement mode: Tensile mode - Test piece width: 5mm Chuck distance: 20mm Heating and cooling process: Heat from 20℃ to 200℃ at a rate of 5℃ / min, then cool from 200℃ to 20℃ at a rate of 5℃ / min. -CTE calculation temperature range: 27℃ to 150℃ during heating process Measurement load: 0.05N The above CTE measurement was carried out twice, and the specimen with the smallest CTE change rate calculated from the following formula was evaluated as having the smallest dimensional change when repeatedly heated. CTE change rate (%) = (CTE of first measurement - CTE of second measurement) / (CTE of first measurement) × 100
[0087] The results of various measurements of the alumina particles are shown in Table 2, and the types of resins used (and their elastic moduli) and the results of various measurements of the resin compositions are shown in Table 3. In the table, "-" indicates that no measurement was performed.
[0088] [Table 2]
[0089] [Table 3]
[0090] The measurement results are discussed below. The resin compositions of samples Nos. 1 to 5, which satisfied the requirements of this embodiment, were able to sufficiently suppress the dimensional change when repeatedly heated (i.e., the CTE change rate was 8.4% or less). On the other hand, the resin composition of sample No. 6, which did not satisfy the requirements of this embodiment, had a CTE change rate of 8.5%, and was unable to sufficiently suppress the dimensional change when repeatedly heated.
Claims
1. alumina particles having OH groups on their surfaces and a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39; A resin composition comprising:
2. The alumina particles have an isolated OH group count of 3.1 / nm 2 The resin composition according to claim 1 , wherein the molecular weight is less than 1.
0.
3. The alumina particles have a specific surface area of 0.20 m 2 The resin composition according to claim 1, wherein the molecular weight is 1 / g or more.
4. The resin composition according to claim 1 , wherein the alumina particles have a ratio (L2 / L1) of a total length L2 of internal grain boundaries to a length L1 of an outer edge of the alumina particles, which ratio is less than 139.1%.
5. The resin composition according to any one of claims 1 to 4 is used. A sheet molding compound having a thickness of 1000 μm or less.
6. Alumina particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39.
Citation Information
Patent Citations
Resin composition, cured product, sealing film, and sealing structure
JP2020200478A